2011
DOI: 10.1088/1748-9326/6/4/045203
|View full text |Cite
|
Sign up to set email alerts
|

Fire impact on carbon storage in light conifer forests of the Lower Angara region, Siberia

Abstract: This study focused on structural analysis of ground carbon storage following fires in light conifer stands of the Lower Angara region (Siberia, Russia). Experimental fires of varying frontal intensity were conducted at Scots pine and mixed larch forests of southern taiga. Considerable amounts of surface and ground forest fuels (21-38 tC ha −1 ) enhanced low-to high-intensity fires. Post-fire carbon storage decreased by 16-49% depending on fire intensity and rate of spread, with depth of burn being 0.9-6.6 cm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Similar data to those presented here are needed for other forest types in Siberia, including the extensive larch and spruce/fir forests. Ongoing studies (Chernykh and Furyaev 2011;Ivanova et al 2011;Valendik et al 2013) are helping to fill this gap. Postfire data from this and other studies (Buryak et al 2011;Zhila et al 2011;Kukavskaya et al 2013a) are required to assess the long-term fire impacts on biomass fuel characteristics, carbon stocks, and vegetation dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar data to those presented here are needed for other forest types in Siberia, including the extensive larch and spruce/fir forests. Ongoing studies (Chernykh and Furyaev 2011;Ivanova et al 2011;Valendik et al 2013) are helping to fill this gap. Postfire data from this and other studies (Buryak et al 2011;Zhila et al 2011;Kukavskaya et al 2013a) are required to assess the long-term fire impacts on biomass fuel characteristics, carbon stocks, and vegetation dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…All plots were burned using line ignition along the windward side to mimic equilibrium fire behavior conditions. Fires were primarily surface fires, but they ranged widely in fire behavior and in fire severity (McRae et al 2006;Ivanova et al 2011). Byram's (1959)…”
Section: Burning Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that low fire occurrence had positive effects on boreal forest's resilience, while high fire occurrence should be avoided in future forest management. However, previous studies showed that low fire occurrences had negative effects on boreal forest ecosystem resilience [36,50]. This difference may be related to response variable selection or analysis of fewer indicators of ecological resilience.…”
Section: Discussionmentioning
confidence: 96%
“…In another work, focused on forest in the Angara region, Ivanova et al (2011) highlight the diverse range of post-fire carbon storage, which can vary by 16 to 49%, depending on the fire intensity, which is directly under the control of weather and climate. This is another example of how weather and climate affect land cover, which in turn feeds back negatively (more reflective young vegetation increases albedo) or positively (black carbon deposition on ice/snow or clouds) to the atmosphere and climate systems.…”
Section: Changes In the Exchange Of Greenhouse Gases (Ghg)mentioning
confidence: 99%